Collaborative Governance Regime (CGR) In Handling Post Disaster Infected Citizens in The Earthquake, Tsunami and Liquifaction in Palu City - Awaluddin Awaluddin; Alwi Alwi; Muhammad Yunus; Gita Susanti (Lafadz Jaya Publisher, 2023)
The purpose of this research is to analyze the Collaborative Governance Regime (CGR) in the management of residents affected by the post-earthquake, tsunami and liquefaction disasters in Palu City. The research method used is a qualitative approach with Miles and Huberman 2014 data analysis consisting of: data collection, data condensation, data presentation, and drawing conclusions. From the research conducted, it can be concluded that the Collaborative Governance Regime (CGR) in handling disaster-affected residents after the earthquake, tsunami and liquefaction disasters have not run optimally. This is because there are components in the Collaborative Governance Regime (CGR) cycle that are not going well.